Pengaruh Digital Visual Marketing Dan Inovasi Layanan Terhaap Keputusan Sewa Busana Adat Sikka Pada Meliana Collection - Loi, Olivia Putri Trivenia; Rangga, Yoseph Darius Purnama; Tokan, Maria Goreti Mao (Jurnal Projemen UNIPA, 2026)
This study aims to analyze the effect of Digital visual marketing and Service Innovation, both partially and simultaneously, on the decision to rent Sikka traditional clothing at Meliana Collection. The background of this research is based on the unstable fluctuations in the number of rental transactions at the object of research, so a strategy is needed that can increase consumer appeal, especially through strengthening visual-based digital marketing and improving service quality. This study uses a quantitative approach with causal associative methods. The population in this study consists of all consumers who have rented traditional clothing at Meliana Collection. Determination of the number of samples was carried out using a probability sampling technique with the Slovin formula at a 10% error level, resulting in 88 respondents as the research sample. Data were collected through the distribution of questionnaires and further analyzed using descriptive analysis, classical assumption tests, multiple linear regression analysis, and hypothesis testing (t-test and F-test) using SPSS version 23 software. The results of the research partially (t-test) show that the Digital visual marketing variable has a positive and significant effect on rental decisions (t-count 2.955> 1.988; Sig 0.004). The Service Innovation variable also has a positive and significant effect on rental decisions and is proven to be the most dominant variable influencing consumer decisions (t-count 11.386 > 1.988; Sig 0.000). Simultaneously (F-test), the two independent variables have a significant combined effect on consumer rental decisions (F-count 77.606>2.71; Sig 0.000). The combination of the Digital visual marketing and Service Innovation variables contributes 64.6% (R Square 0.646) to rental decisions, while the remaining 35.4% is influenced by other factors or variables outside of this research model.